(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article comprehensively analyzes the place of the right to the name of the place of origin of goods in the system of civil law objects. The article discusses the legal mechanisms for the protection of trade names based on geographical indications, as well as the importance of such rights in the framework of civil law and their application at the national and international level. The author of the study highlights the specific features of the rights to the name of the place of origin, including their economic and cultural importance, and the benefits they bring to consumers and producers. The article also considers practical issues related to the registration, protection and use of the names of place of origin. In doing so, the author evaluates the role of this legal institution in the world economy and its development prospects, and at the same time critically analyzes the shortcomings in the existing legislation and practice.